The Parodic Novel „My Uncle” by N. G. Kuzmich and Pushkin’s Novel in Verse „Eugene Onegin” - Warda, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article is devoted to a reworking of Pushkin’s novel in verse Eugene Onegin that was effected in Lodz in 1896. The work, entitled Moi dyadya [My Uncle], was penned by one N. G. Kuzmich (which probably was a pseudonym) and published in „Lodzinskiy listok”, a Russian-language newspaper issued in Lodz. The parodic novel is set in Lodz, and its protagonists are: the uncle, Tatiana and Evgeny. The piece offers a reflection of the realities of the industrial Lodz of the 19th century, as well as hints at Pushkin’s famous work.